Effect of Ultrasonic Shot Peening on Oxidation Behavior of T91 and SS347 Steels in Air and Steam at 650 °C - Mondal D.; Chattopadhyay K.; Singh V. (My University, 2025)
Ultrasonic shot peening (USP) is a relatively new process of surface modification to improve mechanical properties as well as corrosion and high-temperature oxidation resistance of metallic materials. The effect of USP on surface properties and the process of high-temperature oxidation in air and steam environment, following USP of the T91 and SS347 steels, was studied in this investigation. Surface modification by USP was done on the T91 and SS347 steels for different time periods of 0.5, 1.0, 1.5, 2.0 and 3.0 min. Microstructural modification, increase in surface roughness and enhancement in microhardness up to a depth of 300-350 µm were observed due to USP. There was also increment in surface roughness as well as microhardness with USP time duration. Thermogravimetric analysis of the oxidation tests showed parabolic oxidation kinetics at 650 °C for both the steels. Comparatively more protective oxide scales, containing high amount of Cr, were formed on the USP-treated samples. The thickness of the oxide scale was reduced with increase in the USP time duration. Oxidation resistance of the T91 steel at 650 °C, both in air and steam, was improved by the USP treatment. Oxidation resistance of the SS347 steel at 650 °C was also improved for the USP2.0 and the USP3.0 conditions. © 2020, ASM International.